Analisis Buku Tematik II Kelas III Kurikulum 2013 Menyayangi Tumbuhan dan Hewan untuk Pembelajaran Abad Ke-21 - Andari Amalia Syahrial (Jurnal Gentala Pendidikan Dasar, 2022)
This research is based on Pujiriyanto’s perspective (2019) regarding educational theory and learning implementation methods in accordance with the 21st century. The learning process must always be dynamic, which is always able to adapt learning models and activities to the various characteristics of the current students, whose mostly known as the millennial generation (z) today. Unfortunately, the majority of teachers in Indonesia only rely conducting their learning activities from thematic books provided by the government to implement the Curriculum 2013. This issue has risen as many education experts discussed the great difference of learning characteristics between the teachers and students in this era, and this could lead to problems in reaching the goal of Curriculum 2013. Having this concern, this research was needed to be conducted to analyze the learning activities in the Thematic Book II “Menyayangi Tumbuhan Dan Hewan” Grade III Elementary School. The research approach is a qualitative approach and it used qualitative content analysis method. The data of the research are the learning activities that are found in the teacher's and the student's books of the chosen thematic book based on the characteristics for 21st century learning. The results show that the thematic book can no longer meet the characteristics of generation (z) students, thus cannot be used as an effective learning resource that facilitates students to achieve learning goals in curriculum.